Dari Subsidi Petani Menuju Pengelolaan Hutan Bersama Masyarakat di Perum Perhutani BKPH Pare, KPH Kediri - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
PerumPerhutaniperformsforestmanagementprogramby involvingpeople livingnearforestarea.It aimsto helplocalfarmerswiththeireconomicproblemsand, at thesametimetosavecultivationcost.Taungyasystem,in whichpeopleareinvolved in land preparationactivity,is implementedin Kediri area as part of the program. Farmersget incentivesfromthat work,thoughseveralcost variablesare not paid by PerumPerhutani Its excuseis that the farmerswill gainmanyadvantagesfrom the agriculturalcommoditythegrowon the land. Community-BasedForest Managementshould involve all stakeholders, especiallyfarmers,fromplanning,monitoringto evaluatingprocess.Bydoingso, it is expectedthat forest resourcemanagementwill highly ftt local specifics, such as social,cultural,physical,andeconomicaspects.